Cigarette smoking and smoking cessation among older adults: United States, 1965-94. Issue 3 (1997) - Husten, C G; Shelton, D M; Chrismon, J H; Lin, Y C; Mowery, P; Powell, F A
Abstract : OBJECTIVE: To characterise patterns of cigarette smoking and smoking cessation among older adults in the United States. DESIGN: Data from the National Health Interview Surveys (NHIS) 1965-94 were analysed. The NHIS is a cross-sectional survey using a representative national sample. SETTING: In most cases interviews were conducted in the home; telephone interviews were conducted when respondents could not be interviewed in person. PARTICIPANTS: Participants were from a representative sample of the American civilian, non-institutionalised population aged 18 and older. Sample sizes for the years analysed ranged from n = 19, 738 to n = 138, 988 overall, and n = 3806 to n = 12, 491 for those aged 65 years and older. MAIN OUTCOME MEASURES: Using the NHIS data from 1965-94, trends in current smoking and the prevalence of smoking cessation by demographic characteristics among older adults (65 years and older) were assessed and compared with trends among younger adults. A logistic regression analysis was conducted to determine the demographic characteristics of former smokers compared with current smokers among those aged 65 and older. RESULTS: The prevalence of current smoking among 65 year olds and older declined from 1965 to 1994 (17.9% to 12.0%). Although smoking prevalence was lower among older adults than younger adults (aged 18-64), the rate of decline in smoking was slower among older adults. Among older adults, the prevalence of cessation rose with increasing educational attainment, and was consistently higher for men than for women and for whites compared with blacks. After adjustment for demographic factors among older adults who had ever smoked, increasing age and educational attainment were strongly related to the likelihood of being a former smoker. Although there were no racial differences among women, older white (OR = 2.6) and Hispanic (OR = 3.67) men were significantly more likely to be former smokers than older black men. Also, the gender difference in smoking cessation was noted only for whites. CONCLUSIONS: Given the projected increase in the elderly population, the medical and economic consequences of smoking will become a greater burden in the next decades. Therefore, focusing attention on cessation among the elderly is an immediate and urgent priority for public health professionals and clinicians.